The Augmented and Virtual Reality in HRM Development - Farid Wadjdi; Yuliza Yuliza (Postgraduate, University of Mataram, 2023)
The purpose of this study is to describe the use of virtual and augmented reality in the field of HRM. The growing interest in virtual and augmented reality applied to HR development. The application of virtual and augmented reality to human resources management and development is also underway. This review is literature study with an elaborative approach. This approach is a methodological effort by organizing the logic flow of the discussion with various compatible literature sources. Reliable literature sources come from journals, books, articles, and other sources relevant to this discourse. The results show that virtual and augmented reality in human resources management and development is still in a very early stage, requiring more in-depth research. This study found that VR and AR can be successfully used in improving workers’ productivity, enhancing employee training, reducing costs, making worksites safer and closing the skills gap more effectively and efficiently.